Panel Data Analysis of Economic Growth Determinants in Ecowas Region - A. I, Adewole; F. F, Amurawaye (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
The study examined the Macroeconomic factors influencing Economic Growth in Economic Community of West African States region using panel data regression. A Pooled ordinary least squares, Fixed Effect Model, and Random Effect Model were implemented to fit the panel regression model for the panel data sets. The result showed that estimates from fixed effect model were accurate in determining the econometric relationship among the variables under study. According to fixed effect model chosen for the dataset under study, Foreign direct investment, Exchange rate, Export of goods and services and Inflation rate are statistically significant. The variables Foreign direct investment, Inflation rate and External debt have positive impact while the Exchange rate and Export of goods and services variables affect the Economic Community of West African States Countries negatively. Policy makers are therefore advised to erect anti-inflationary policies that attract Foreign Investors, emphasis should be laid on encouraging stable and reasonable exchange rate to promote even and sustainable Economic Growth.